Polymer-Dependent Performance of Mucoadhesive Chlorhexidine Gels: A Comparative Evaluation of HPMC and Chitosan Formulations: Mucoadhesive CHX Gels Using HPMC and Chitosan - Salsabilian, Puria; Ahmadinia, Mahdi; Jafariazar, Zahra; Saffari, Mostafa (Iranian Journal of Pharmaceutical Sciences, 2026)
Chlorhexidine (CHX) is a widely used antiseptic agent in oral healthcare. However, conventional mouthwash formulations are limited by poor retention time on mucosal surfaces. This study aimed to develop and compare two mucoadhesive CHX 0.2% gels using Hydroxypropyl Methylcellulose (HPMC) and chitosan polymers to improve drug retention and release performance. Two gel formulations were prepared using HPMC and chitosan as the polymeric base. Their physicochemical properties (pH, viscosity, spreadability), rheological behavior, mucoadhesive strength, in vitro drug release, antimicrobial activity against Staphylococcus aureus and Escherichia coli, and six-week stability were evaluated using validated protocols. Drug release kinetics were modeled using Korsmeyer–Peppas and Higuchi equations. Both gels exhibited pseudoplastic rheology and remained stable throughout storage. The HPMC gel had lower viscosity and greater spreadability, resulting in faster drug release. The chitosan gel demonstrated significantly stronger mucoadhesive strength and sustained drug release over 8 hours. Antimicrobial activity was comparable between formulations. No significant changes in pH or viscosity were observed during the stability period. Both polymers are suitable for CHX gel formulation, with HPMC offering ease of application and rapid release, while chitosan provides superior mucoadhesion and prolonged release. These findings support further in vivo evaluation and highlight the potential of polymer-based CHX gels as improved alternatives to traditional mouthwashes in oral infection management.